Peran Barrier Memoderasi Pengaruh Motivasi dan Enabler terhadap Perilaku Berbagi Pengetahuan Pegawai - Ilafi Rani Yoasti; Hedwigis Esti Riwayati; Ovalia; Muhammad Iqbal (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to investigate and analyze the effect of motivation, enabler and enabler on knowledge sharing behavior in Ministry of Finance with barrier as moderating variable. This study adopts a quantitative method with a sample of 100 employees of Ministry of Finance. The data employed are primary data derived from questionnaire. Moderated Regression Analysis (MRA) is used to analyse the data. From the results of the study, it was found that motivation and enabler had a significant and positive effect on the knowledge sharing behavior of Ministry of Finance employees. The results also showed that the barrier did not moderate the influence of motivation or enabler on the knowledge sharing behavior of MoF employees.